IGFBP7 regulates sepsis‐induced acute kidney injury through ERK1/2 signaling. Issue 5 (18th November 2018) - Wang, Xiaolin; Ma, Teng; Wan, Xiaojian; Meng, Yan; Zhao, Zhenzhen; Bian, Jinjun; Bao, Rui; Deng, Xiaoming; Yang, Tao
Abstract: IGFBP7 as an early biomarker has been used to identify patients at risk of developing acute kidney injury (AKI). Nevertheless, its role in AKI remains obscure. The aim of our study is to determine the role and mechanism of IGFBP7 in lipopolysaccharide (LPS)‐induced HK‐2 cells in vitro and on sepsis‐induced AKI by cecal ligation and puncture (CLP) in vivo. Here, we identified that IGFBP7 expression was increased in patients with AKI and HK‐2 cells with LPS (1, 2, and 5 μg/mL) induction. HK‐2 cells with LPS induction showed cell cycle arrest at G1‐G0 phases and cell apoptosis and activated ERK1/2 parallel with the changes in the proteins belonging to the ERK1/2 pathway, including Cyclin D1, P21, Bax, and Bcl‐2, which were inhibited by the IGFBP7 knockdown. Moreover, IGFBP7 overexpression significantly induced cell cycle arrest at G1‐G0 phases and cell apoptosis of HK‐2 cells, which were inhibited by PD98509, an ERK1/2 signaling inhibitor. IGFBP7 knockdown effectively alleviated the severity of the renal injury, evidenced by decreases in the urinary levels of creatinine, blood urea nitrogen, and albumin, cell apoptosis, and activation of ERK1/2 signaling in CLP mice. Taken together, our findings indicate that IGFBP7 regulates sepsis‐induced AKI through ERK1/2 signaling. Abstract : IGFBP7 levels were increased in the urine of AKI patients and in LPS‐induced HK‐2 cells. IGFBP7 silencing inhibited LPS‐induced apoptosis and cell cycle arrest in HK‐2 cells and cecal ligation and puncture (CLP)‐induced AKI in mice. ERK1/2 signaling is associated with the IGFBP7‐mediated injury in HK‐2 cells.